PENGARUH PERMAINAN TRADISIONAL TERHADAP MINAT PESERTA EKSTRAKURIKULER TAEKWONDO SMA YADIKA 13 BEKASI - Tio Wijaya; Rhama Nurwansyah Sumarsono; Ardawi Sumarno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of traditional games on the interest of taekwondo extracurricular participants at Yadika 13 Bekasi High School. The method used is experimental with a quantitative approach. The study population consisted of 30 students who were members of taekwondo extracurricular activities, which were taken using the total sampling technique. This research design uses a Pre-Experiment with a One-Group Pretest-Posttest model. The instrument used for data collection is a questionnaire of interest in practicing, with a Mean Pretest value of 79.90 and a Mean Posttest value of 82.07. Hypothesis testing using Paired Sample t-test gives a significance value (2-tailed) of 0.001 <0.005, indicating a significant influence between the values before and after treatment. Thus, it can be concluded that traditional games have a positive influence on interest in practicing in taekwondo extracurricular activities at Yadika 13 Bekasi High School.